Alkali lignin degradation with aqueous ammonium-based ionic liquid solutions. (10th June 2020) - Tolesa, Leta Deressa; Gupta, Bhupender S.; Tiwikrama, Ardila Hayu; Wu, Yi-Chen; Lee, Ming-Jer
Abstract: In this work, we developed a green route to increase the added value of the lignocellulose material. Our proposed method involves ammonium-based ionic liquid selective fractionation of the lignin into essential poly-hydroxy or phenolic compounds. The selected ionic liquids (ILs) are di -isopropylethylammonium chloride ([DIPEA][Cl]) and di- isopropylethylammoniumbenzoate ([DIPEA][Bn]). The depolymerized solution was characterized by chromatographic (GPC and GCMS) and spectroscopic (FT-IR, 1 HNMR and 13 CNMR) techniques. The results of the analysis proved that the polymeric structure of lignin is converted into its monomers and oligomers. This confirms the potentiality of [DIPEA][Cl] and [DIPEA][Bn] ILs for the conversion of lignin into valuable aromatic compounds. In addition, our study reveals the bi-functional nature (solvation medium + catalytic agent) of the selected ILs for the depolymerization of the lignin. Since lignin is well recognized as a suitable resource for the essential chemicals, therefore, the present study is very useful in refining an alternative source for the clean production of the valuable chemicals. Graphical abstract: Image 1 Highlights: Depolymerization of alkali lignin in aqueous solutions of two ammonium-based ionic liquids is investigated. Ionic liquids [DIPEA][Cl] and [DIPEA][Bn] serve as catalyst as well as green solvent in depolymerization process. Heating at 170 °C for 60 min found as the favorable conditions for both two ILs systems. The average MWs are reduced by 71.1% and 84.8% after treating with [DIPEA][Cl] and [DIPEA][Bn], respectively. Monomers and oligomers of lignin were detected in the depolymerized solution.